Accuracy of Invisalign® aligners in adult patients: a retrospective study of angular tooth movements - Raquel Bueno MEDEIROS; Renata Faria SANTOS; Jose Augusto MENDES-MIGUEL; Eduardo Kant Colunga ROTHIER; Fausto Medeiros MENDES; Gladys Cristina DOMINGUEZ (Dental Press Editora, 2024)
ABSTRACT Objective: This retrospective study aimed to assess the predictability of Invisalign® aligners regarding rotational, mesio-distal and buccal-lingual tip movements. Methods: Two materials were included in the analysis - EX30, used until 2013; and SmartTrack, in current use. The study comprised 56 adult patients treated with Invisalign Comprehensive. Data sample were assessed on three sets of digital models; model 1 - initial, model 2 - predicted, and model 3 - achieved. Sixty reference points were marked in each dental arch, and two reference planes assisted the superimposition. The degree of rotation, mesio-distal and buccal-lingual tip was obtained via trigonometric calculations, through a previously published validated method. The accuracy of outcomes was compared according to the types of tooth movement and teeth groups,and the influence of predetermined variables on movement accuracy was also investigated. Results: Rotation and mesio-distal tip did not present any significant difference when comparing EX30 and SmartTrack groups. Only buccal-lingual tip presented a significant difference, incisor and canine groups treated with EX30 aligners presented an increase in accuracy (p= 0.007 and p = 0.007, respectively). For each additional degree planned for rotation movements, there was an increase of 0.35° in the discrepancy, and an increase of 0.40° and 0.41° for mesio-distal and buccal-lingual tip, respectively. EX30 and SmartTrack discrepancies were compared by multilevel linear regression. Conclusion: EX30 aligners reached higher accuracy for buccal-lingual tip in anterior teeth. However, for rotation and mesio-distal tip, SmartTrack and EX30 are similarly accurate. The total amount of planned movement has a significant impact on accuracy rates, with a decrease in accuracy for every additional degree.